Teaching Reading on English for Specific Purposes with Think-Pair-Share Technique - Fatchul Mu’in; Rizky Amelia; Raisa Fadilla; Eka Puteri Elyani (Universitas Bengkulu, 2020)
Different departments in a university have different terms with general English. English for Specific Purpose (ESP) helps students with different departments learn specific terms. Social studies study program is one of the majors that its students find it rather hard to comprehend the content and terms related to their major. Think-Pair-Share (TPS) on reading helps develop students' ability to understand the text. This study is aimed to find out the difference between the students who are taught using ESP text with Think-Pair-Share (TPS) Technique and those who are not taught with the TPS technique. This study employs a quasi-experimental design. The study objects were the students of the social studies study program, which were classified into experimental and control groups. The research instruments were related to social studies in English passages. Posttest data were calculated and used to determine the treatment's effectiveness or any significant difference in each group. The data were analyzed by an analysis of variance (ANOVA) to test the hypotheses. The study results reveal that experimental and control classes have a significant difference in the mean; 76.63 is an experimental group mean that was higher than the control group mean that was 74.64. It shows that the students who used the Think-Pair-Share technique had better reading comprehension on ESP text than the students who did not use the technique. This is due to the implementation's steps that emphases students' performance and togetherness on doing their activities in the classroom activities to develop their ability in language skills. This study is expected to provide new insight into English for specific purposes and give valuable experience in teaching reading for specific social studies. This research is also proposed some new vocabularies related to social studies to the students. Thus, this study gives sight and information about English reading texts based on social studies.